Study of Asphalt Binder’s Rheological Properties Extracted from Warm Mix Asphalts - Morea, Francisco (2018)
The long-term performance of Warm Mix Asphalts (WMAs) is relatively unknown because this technology is fairly new. A critical question is how much the production temperature can be cut down in these mixtures without reducing performance and durability. In order to answer such a question, it is necessary to study different variables, such as type of warm additive and sort of binder, in relation to temperature reduction and how they all can influence and limit the mixture behavior. The study of rheological properties of "warm" binders related to pavement failure (fatigue and rutting) is a way to explore the potential performance of WMA. This work examines the rheological properties of different asphalt binders extracted from WMAs that were elaborated at temperatures 20°C and 30°C lower than hot mix asphalts. WMAs were produced with two different warm mix additives and two types of asphalt binders (one straight-run and one polymermodified). The results show that rheological properties of WMA binders with a 20°C temperature reduction were similar or slightly better than those of the control asphalt binders in the case of modified asphalt. The warm straight-run binders present a worse rutting response, independent of the type of additive used. With a 30°C temperature reduction, no improvements were reached for either type of warm binder.